Organizational justice mediates the relation between police officers’ metaperceptions of objectification and health and well-being - Correia, I. (2023)
This article intends to contribute to the study of the relation between workers’ metaperceptions of objectification and their health and well-being, further testing the possibility that this relation might be mediated by a decrease in perceived organizational justice. The sample of the present study was composed by 573 police officers who voluntarily consented to answer to an anonymous online survey. Self-reported measures of the police officers’ metaperception of objectification by their superior, organizational justice, and health and well-being were collected. It was found that the metaperception of objectification by the superior was associated with a decrease in health and well-being. Furthermore, the association between the metaperception of objectification by the superior and health and well-being was fully mediated by the decrease in perceptions of organizational justice. These results establish a theoretical relation between these three areas of research, and open important avenues for practice and future research.